Gambaran Perilaku Remaja Putri Terhadap Hygiene Genetalia Saat Menstruasi Pada Siswi Kelas X di SMA Negeri 5 Denpasar Tahun 2016 - Noriani, M.Kes, Ni Ketut; Nurtini, Ni Made (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2018)
Knowledge greatly affect a person’s behavior. Lack of knowledge of young women against genital hygiene, especially during menstruation will cause reproductive problems such as infection, itching, redness, vaginal discharge, bad odor etc. The purpose of this study was to determine the relationship of the level of knowledge of the behavior of young women against genital hygiene during menstruation in female students of SMP Negeri 5 Junior High School Denpasar in 2016. This studyused analytical design with cross-sectional approach. The subjects were all 8th year students of SMA Negeri 5 Junior High School Denpasar Sampling used non-probability sampling with saturated sampling technique. The number of samples in this study was 78 respondents. Data collection tool was a questionnaire. Data analysis techniques used statistical test of Spearman Rho. This results showed that a significant level <0.05, p value<0.001 and direction of a positive correlation (+) and correlation strength 0.385 meaning lower levels of relationship. Then Ho was rejected but Ha was accepted which means there was a correlation between the level of knowledge of the behavior of young women about genital hygiene during menstruation. It can be concluded that the higher the level of knowledge of young women the better the genital hygiene behavior. The reverse was also true the less the level of knowledge of young girls, the more bad genital hygiene behavior. It suggested that the students should maintain good genital hygiene behavior.